2016
DOI: 10.1108/jcs-11-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Kundalini yoga as mutual recovery: a feasibility study including children in care and their carers

Abstract: Purpose The purpose of this paper is to test whether incorporating a 20-week Kundalini yoga programme into a residential home for children improves well-being outcomes. Design/methodology/approach This is a mixed methods feasibility study. Feasibility was assessed through recruitment and retention rates as well as participants’ self-report perceptions on social inclusion, mental health and well-being and through semi-structured interviews on the benefits of the study. Mutual recovery entailed that children i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(43 reference statements)
0
9
0
2
Order By: Relevance
“…The concept of mutuality is central to this capoeira paper too. Further, regarding yoga, Perez et al (2016) conducted a mixed methods feasibility study to test whether incorporating a twenty week Kundalini yoga programme, where both children and staff took part, into a residential home for children improved well-being outcomes. In terms of findings 'all the participants reported that the study was personally meaningful and experienced both individual (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of mutuality is central to this capoeira paper too. Further, regarding yoga, Perez et al (2016) conducted a mixed methods feasibility study to test whether incorporating a twenty week Kundalini yoga programme, where both children and staff took part, into a residential home for children improved well-being outcomes. In terms of findings 'all the participants reported that the study was personally meaningful and experienced both individual (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Research involving compassion-based interventions also revealed the maintenance of changes (Irons & Heriot-Maitland, 2020 ; Matos et al, 2022a ) or continued improvements in depression symptoms at follow-ups (Ferrari et al, 2019 ). Other programs designed for the RYC setting, using other theoretical frameworks, did not show significant improvements on burnout (Donald, 2015 ) and mental health (Vallejos et al, 2016 ). Hence, both the compassion training and its theoretical framework seem a promising approach to counteract burnout, anxiety, and depression on caregivers, helping to improve their functioning and the quality of the care they provide.…”
Section: Discussionmentioning
confidence: 96%
“…Altogether, the above-mentioned demands reinforce the need to offer proper training to support caregivers in high-stress work environments, as it is the case of RYC (Barford & Whelton, 2010 ; McElvaney & Tatlow-Golden, 2016 ). Although some studies tried to overcome this need, some limitations still persist: (1) existing research showed that interventions didn’t had the expected impact (Donald, 2015 ; Silva & Gaspar, 2014 ; Vallejos et al, 2016 ); (2) when positive effects on stress and related syndromes were reached, those studies presented methodological limitations, such as small sample size, lack of randomization and/or absence of control group (Hidalgo et al, 2016 ; Schmid et al, 2020 ; Turner, 2017 ; van Gink et al, 2018 ); (3) programs were specifically tailored to babies homes (St. Petersburg–USA Orphanage Research Team, 2008 ). Some trauma-informed approaches also addressed staff mental health.…”
Section: Introductionmentioning
confidence: 99%
“…9-10-11 A percepção dos participantes sobre a Kundalini Yoga no ambiente escolar revelou que o yoga propicia espaço de tranquilidade. 19 Os participantes ganham acesso às experiências dos outros e suas respostas aos exercícios criam momentos para empatia, união social, tranquilidade e sensação S de proximidade com os semelhantes, o que contribui para a sensação de bem-estar relatada pelos participantes. Já os aspectos mais dinâmicos do yoga, como os exercícios posturais e a respiração, combinados com o relaxamento, aprimoram os efeitos positivos da saúde mental, conforme identificado em vários dos relatos.…”
unclassified
“…Já os aspectos mais dinâmicos do yoga, como os exercícios posturais e a respiração, combinados com o relaxamento, aprimoram os efeitos positivos da saúde mental, conforme identificado em vários dos relatos. 19 Além disso, o benefício da Kundalini Yoga no controle da ansiedade também foi relatado pelos participantes. O yoga é munido de um vasto arsenal de meditações, em que muitos deles foram descobertos como específicos para tratamentos de transtornos psiquiátricos.…”
unclassified